(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
How to approach curation in the Performing Arts through the lens of theories and experiences from the periphery of capitalism? This study addresses this question by analyzing the editions of the Mostra Internacional de Teatro de São Paulo from 2016 to 2020, using a framework that critiques colonial legacies and anticipates decolonization. In this context, the curatorial field emerges as a contested space where institutional pressures from the art market intersect with the demands of social movements aiming to transform the world as we know it.